2010
DOI: 10.1088/0004-637x/714/2/1256
|View full text |Cite
|
Sign up to set email alerts
|

The Calibration of Monochromatic Far-Infrared Star Formation Rate Indicators

Abstract: 1 Based on observations obtained with the Spitzer Space Telescope, which is operated by JPL, CalTech, under NASA Contract 1407.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
526
6
9

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 351 publications
(581 citation statements)
references
References 129 publications
31
526
6
9
Order By: Relevance
“…We notice that the 100 μm relation is nearly linear, whereas the 160 μm relation is slightly superlinear. This is similar to what Calzetti et al (2010) found (Eq. (23)), even though individual star-forming regions probe a much smaller range of Σ SFR .…”
Section: μM and 160 μM As Sfr Estimatorssupporting
confidence: 92%
See 3 more Smart Citations
“…We notice that the 100 μm relation is nearly linear, whereas the 160 μm relation is slightly superlinear. This is similar to what Calzetti et al (2010) found (Eq. (23)), even though individual star-forming regions probe a much smaller range of Σ SFR .…”
Section: μM and 160 μM As Sfr Estimatorssupporting
confidence: 92%
“…For comparison additional integrated galaxies are also plotted: SINGS (Spitzer Infrared Nearby Galaxies Survey, Dale et al 2007, red crosses), LVL (Local Volume Legacy survey, Dale et al 2009, green squares), starburst galaxies from Engelbracht et al (2008) (blue triangles) and LIRGs (luminous infrared galaxies, Calzetti et al 2010, cyan circles). These galaxies belong to the high-metallicity bin of Calzetti et al (2010), which encloses the metallicity of M 33 (Magrini et al 2010). The best fit of selected star-forming regions in M 33, taking into account the uncertainties on both axes, is plotted with a solid black line.…”
Section: Flux Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, the vast majority of the starforming spirals identified by Herschel and Spitzer lie in the blue cloud, indicating that, at least in the cluster core, the identification of red sequence and blue cloud populations with passive and star-forming galaxy populations is largely valid in the infrared. We used the star formation rate (SFR) calibration of Calzetti et al (2010), which uses L(24 μm) and L(Hα) to measure the obscured and unobscured components of star formation in a galaxy. The Hα luminosities of each galaxy were obtained using Eq.…”
Section: Spatial Distribution Of Star-forming Galaxiesmentioning
confidence: 99%